The Effect of the Impact of Digital Transformation Strategy on Financial Performance Moderated by Cognitive Conflict in Partner Companies of PT. Erdiva Daya Technology Solutions - Setiawan, Taufik; Widhianto, Chandra Wibowo (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study aims to verify whether digital transformation strategy (DTS) enhances organizational performance and to analyze the necessity of implementing DTS, considering perspectives like "Skewed conflict," "minority dissent theory," and the "too-much-of-a-good-thing" principle. This research uses a quantitative method with a descriptive and explanatory survey approach to examine the cause-and-effect relationship between variables. The research concludes that DTS significantly influences both short-term and long-term financial performance, providing insights into how cognitive conflict influences DTS effectiveness and highlighting the need for enterprises to manage such conflicts to maximize financial performance.